Behavior of sulfentrazone in the soil as influenced by cover crop before no-till soybean planting - Macedo, Gabrielle de Castro [UNESP]; Carbonari, Caio Antonio [UNESP]; Velini, Edivaldo Domingues [UNESP]; Gimenes Cotrick Gomes, Giovanna Larissa [UNESP]; Alves de Matos, Ana Karollyna [UNESP]; Castro, Edicarlos Batista de [UNESP]; Burgos, Nilda Roma (Cambridge Univ Press, 2020)
More than 80% of soybean [Glycine max (L.) Merr.] in Brazil is cultivated in no-till systems, and although cover crops benefit the soil, they may reduce the amount of residual herbicides reaching the soil, thereby decreasing herbicide efficacy. The objective of this study was to evaluate sulfentrazone applied alone, sequentially after glyphosate, and in a tank mixture with glyphosate before planting no-till soybean. Experiments were performed in two cover crop systems: (1) pearl millet [Pennisetum glaucum (L.) R. Br.] and (2) forage sorghum [Sorghum bicolor (L.) Moench ssp. bicolor]. The treatments tested were: glyphosate (720 g ae ha(-1)) at 20 d before sowing (DBS) followed by sulfentrazone (600 g ai ha(-1)) at 10 DBS; glyphosate + sulfentrazone (720 g ae ha(-1) + 600 g ai ha(-1)) for cover crop desiccation at 10 DBS; and sulfentrazone alone at 10 DBS without a cover crop. The accumulation of straw was 31% greater using sorghum rather than pearl millet. In the sorghum system, the concentration of sulfentrazone at 0 to 10 cm was 57% less with sequential application and 92% less with the tank mixture compared with the treatment without cover crop straw at 1 d after application (DAA). The same occurred in the pearl millet system, where the reduction was 33% and 80% for the sequential application and tank mixture, respectively. The absence of a cover crop resulted in greater sulfentrazone concentrations in the top layer of the soil when compared with the sequential application or tank mixture. At 31 and 53 DAA, the concentration of sulfentrazone at 10 to 20 and 20 to 40 cm did not differ among treatments. Precipitation of 90 mm was enough to remove the herbicide from the cover crop straw at 31 DAA when using sequential application. An additional 90-mm precipitation was necessary to promote the same result when using the tank mixture.
Keywords: Dystrophic Red Nitosol; glyphosate [N-(phosphonomethyl)glycine]; leaching; pearl millet (Pennisetum glaucum (L; ) R; Brown); sorghum [Sorghum bicolor (L; ) Moench ssp; bicolor]; sorption